2018
DOI: 10.1111/bpa.12587
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin III is a key component of α‐synuclein fibrils in Lewy bodies of PD brains

Abstract: Lewy bodies (LB) and Lewy neurites (LN), which are primarily composed of α-synuclein (α-syn), are neuropathological hallmarks of Parkinson's disease (PD) and dementia with Lewy bodies (DLB). We recently found that the neuronal phosphoprotein synapsin III (syn III) controls dopamine release via cooperation with α-syn and modulates α-syn aggregation. Here, we observed that LB and LN, in the substantia nigra of PD patients and hippocampus of one subject with DLB, displayed a marked immunopositivity for syn III. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 67 publications
(95 reference statements)
7
29
0
Order By: Relevance
“…[3][4][5] We recently described that the synaptic phosphoprotein synapsin III (Syn III) interacts and cooperates with aSyn in the control of DA release from mesencephalic neurons. [6] Moreover, we showed that Syn III is another key component of aSyn insoluble fibrils extracted from the post-mortem brains of sporadic PD patients [7] and that Syn III is a crucial mediator of aSyn aggregation and toxicity. [8] Strikingly, our most recent findings suggest that threo-methylphenidate (MPH), a monoamine re-uptake inhibitor clinically approved for the treatment of attention deficits and hyperactivity disorder (ADHD) [9] and for ameliorating gait freezing in advanced PD, [10][11][12][13][14] is able to stimulate an aSyn/Syn III-mediated locomotor response, specifically in aSyn transgenic mice at a pathological stage that exhibit severe dopaminergic functional deficits.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[3][4][5] We recently described that the synaptic phosphoprotein synapsin III (Syn III) interacts and cooperates with aSyn in the control of DA release from mesencephalic neurons. [6] Moreover, we showed that Syn III is another key component of aSyn insoluble fibrils extracted from the post-mortem brains of sporadic PD patients [7] and that Syn III is a crucial mediator of aSyn aggregation and toxicity. [8] Strikingly, our most recent findings suggest that threo-methylphenidate (MPH), a monoamine re-uptake inhibitor clinically approved for the treatment of attention deficits and hyperactivity disorder (ADHD) [9] and for ameliorating gait freezing in advanced PD, [10][11][12][13][14] is able to stimulate an aSyn/Syn III-mediated locomotor response, specifically in aSyn transgenic mice at a pathological stage that exhibit severe dopaminergic functional deficits.…”
Section: Introductionmentioning
confidence: 93%
“…For the synthesis of 2, the PEG linker is introduced using Mitsunobu reaction conditions with 4 to give N-Boc-amino-PEG4-alcohol (7). Both the amines of 7 are then deprotected under acidic conditions, to give 8, which is then reacted with commercial 6-COOH-TAMRA, using a TSTU-based amide coupling protocol.…”
Section: Chemistrymentioning
confidence: 99%
“…In this context, our results suggest that droplet formation by a-synuclein may be involved in a physiological mechanism to cluster synaptic vesicles, possibly in conjunction with other proteins such as synapsins, which have also been shown to phase-separate into liquid-like assemblies [55]. Indeed, synapsins are implicated in synaptic function in conjunction with synuclein [57,58] and are components of Lewy bodies [59].…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have demonstrated the use of PLA to study αSyn interacting with other proteins, such as the dopamine transporter and αSyn complexes in a tg mouse overexpressing αSyn 1–120 ( 20 ). Interactions with TOM20 ( 21 ) and the synaptic protein synapsin III ( 22 , 23 ) have also been observed with PLA. In addition, PLA has been used to specifically detect oligomeric αSyn in brain tissue from PD patients ( 24 ).…”
Section: Discussionmentioning
confidence: 91%